Legal Protection for Buyers against the Understanding of Home Ownership Loans - Evie Pravitasari; Aryani Witasari (Sultan Agung Notary Law Review, 2021)
Subsidized Home Ownership Loans are loans intended for lower-middle income communities in order to meet housing needs or repair houses that they already own. KPR is a credit facility provided by the Bank as a creditor to consumers (buyers) as debtors which are used to purchase land and houses on it. The approach used in this study is a normative juridical approach. The results of this study are: 1) Legal protection for buyers in cases of buying and selling houses and land under the hands can be obtained by submitting an application for determination to the local district court to ratify the buying and selling process, 2) The validity of buying and selling which aims to take over ownership credit house under the hand is not binding on third parties. In connection with this, according to law the legal owner of the land and building is the owner of the first party so that the transfer of rights must go through/obtain the approval of the first party. This makes it difficult in the future, especially if the owner's whereabouts are known.